Sistem Monitoring dan Kontrol Katup Pendingin terhadap Temperatur Air Outfall PLTU - Marina Artiyasa; Anang Suryana; Muhammad Shobirin; Anggy pradiftha junfithrana; Aryo de Wibowo Muhamad Sidik; Mochtar Ali Setyo Yudono; Edwinanto Edwinanto (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
The Pelabuhan Ratu Steam Power Plant (PLTU) is a large-scale power plant that generates a lot of heat energy. Sea water is one of the cooling systems or cooling systems that can be used, but the continuous use of sea water as a cooling system media at the power plant has a negative impact because if the cooling system output water has a hot temperature that exceeds the provisions, it will disrupt marine life near the water disposal area. A cooling system, also known as an outfall or downstream channel. In order to address these issues, a study titled the monitoring and control system of the cooling valve on the outfall water temperature of the Pelabuhan Ratu PLTU with Fuzzy Tsukamoto was conducted. The goal of this study is to create a prototype of an Internet of Things (IoT)-based cooling valve system. The main device connected to the internet is the Nodemcu ESP8266 microcontroller, and two DS18B20 temperature sensors are used to measure the water temperature, as well as the Tsukamoto Fuzzy method to control the water-cooling servo valve downstream of the channel. The research results from the prototype design of the cooling valve system were successful, and the system is able to control the server motor that is connected to the outfall water temperature cooling valve using the input value from the DS18B20 temperature sensor, with a 90% success rate. The output of this system can be monitored and controlled using the Tsukamoto Fuzzy method. With the implementation of this system, it is possible to keep the outfall water temperature below the maximum threshold set by the Ministry of Environment and Forestry.